Na tropie społecznej przynależności adresatów kazań Józefa Męcińskiego (XIX w.) - analiza wyborów językowostylistycznych = On the track of social affiliation of the recipients of sermons by Joseph Męciński (XIX c.) - the analysis of linguistic and stylistic choices - Pałucka-Czerniak, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of the deliberations was to determine the recipient of sermons by Joseph Męciński on the basis of the linguistic and stylistic analysis of the texts from various preaching volumes of the same author. The conducted studies aim at verifying common opinions about motivating stylistic choices by the affiliation of the speech addressee to the peasant state.
Keywords: tożsamość; tożsamość aktywna; tożsamość pasywna; tożsamość deliberatywna; memetyka; identyfikacja; samoidentyfikacja; język; językoznawstwo; językoznawstwo polskie